PERTANGGUNGJAWABAN PIDANA TERHADAP KARYAWAN PELAKU TINDAK PIDANA PENGGELAPAN UANG DI PERUSAHAAN PT. ANEKA NIAGA DI KOTA KUPANG - Nenobais, Yosefina Sarlin; Wilhelmus, Bhisa V; Fanggi, Rosalind A (Petitum Law Journal, 2025)
This research discusses criminal responsibility and the application of legal sanctions against an employee of PT Aneka Niaga in Kupang City who was involved in the criminal act of embezzling company funds. This case involves AAF, an employee authorized to collect payments from customers in Rote and Sabu Districts, who misused funds amounting to IDR 135,568,090 for personal interests, including online gambling. This research uses empirical juridical methods with an empirical legal approach, analyzing legal provisions in Articles 372-376 of the Criminal Code (KUHP), Law no. 31 of 1999 concerning Eradication of Corruption Crimes, and Law no. 13 of 2013 concerning Employment. The findings show that the perpetrator fulfills the elements of embezzlement in a position of trust as regulated in Article 374 of the Criminal Code, which includes the existence of the perpetrator, the ability to be held accountable, malicious intent, and no justification. Although the perpetrator was also involved in online gambling, the judge decided to impose a sentence based on the embezzlement charge, imposing a prison sentence of 2 years and 6 months, while considering online gambling as an aggravating factor. This research concludes that law enforcement needs to be increased more firmly and proportionally to create a deterrent effect, and companies must strengthen internal supervision to prevent abuse of authority by employees.